Adherence to guidelines for androgen deprivation therapy after radical prostatectomy: Swedish population-based study. (3rd May 2020) - Lycken, Magdalena; Drevin, Linda; Garmo, Hans; Larsson, Anders; Andrén, Ove; Holmberg, Lars; Bill-Axelson, Anna
Abstract: Background: Androgen deprivation therapy (ADT) is a non-curative but essential treatment of prostate cancer with severe side effects. Therefore, both over- and underuse should be avoided. We investigated adherence to guidelines for ADT following radical prostatectomy through Swedish population-based data. Material and methods: We used the database Uppsala/Örebro PSA cohort (UPSAC) to study men with localised or locally advanced prostate cancer at diagnosis (clinical stage T1–T3, N0–NX, M0–MX, and prostate-specific antigen (PSA) <50 ng/ml) who underwent radical prostatectomy 1997–2012. 114 men were treated with ADT and selected as cases; 1140 men with no ADT at the index date were selected as controls within 4-year strata of year of radical prostatectomy. All men with a biochemical recurrence and a PSA doubling time <12 months and/or a Gleason score of 8–10 were considered to have an indication for ADT according to the European Association of Urology (EAU) guidelines. Results: No indication for ADT was found in 37% of the cases. Among these, 88% had clinical stage T1–2 at diagnosis, 57% had a biopsy Gleason score 2–6, 98% had an expected remaining lifetime over 10 years, 12% received castration, and 88% received antiandrogen monotherapy. 2% of controls were found to have an indication for ADT, and 96% of these had an expected remaining lifetime over 10 years. Conclusion: Our results indicate that overtreatment with ADT after radical prostatectomy is common, whereas undertreatment is unusual. Interventions to improve adherence to guidelines are needed to avoid unnecessary side-effects and long treatment durations with ADT.